2021
DOI: 10.1007/s40135-021-00274-0
|View full text |Cite
|
Sign up to set email alerts
|

Optic Pit Maculopathy: Clinical Features and Management Options

Abstract: Purpose of ReviewIn this article, we review the pathogenesis, clinical features, imaging modalities, and latest management options for optic pit maculopathy (OPM). Recent FindingsThe pathogenesis of OPM remains to be unclear, but imaging tools such as optical coherence tomography (OCT) and OCT angiography are enhancing our knowledge. Observation continues to be the best management strategy for patients with good visual acuity, and many cases have demonstrated spontaneous resolution. For more advanced, progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 100 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…There is still no unified opinion among ophthalmologists about the treatment of this condition. The observation of such patients, without any additional treatment, indicated that spontaneous regression of the maculopathy occurs over time in as many as 25% of cases [8,19].…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…There is still no unified opinion among ophthalmologists about the treatment of this condition. The observation of such patients, without any additional treatment, indicated that spontaneous regression of the maculopathy occurs over time in as many as 25% of cases [8,19].…”
Section: Discussionmentioning
confidence: 98%
“…The appearance of maculopathy associated with OP is a frequent manifestation, it is found in 84% of patients, especially those where OP is located temporally. As many as 20% of patients with OPM are asymptomatic, and the remaining symptoms usually present between the third and fourth decade of life, however, cases with a much earlier onset have also been described [4,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The principle is that light can damage the endothelial cells and stroma of CNV, thereby reducing its metabolic activity and thereby inhibiting its growth and development [48][49][50] Maculopathy Activate retinal cells: Light (670 nm) stimulates the metabolic activity of retinal cells and increases the energy level of cells, thus contributing to the regeneration and repair of cells in the macular area. Elimination of free radicals: the occurrence of macular lesions is related to free radical damage, and light can eliminate free radicals, reduce the degree of cell damage, and slow the occurrence and progress of macular lesions Use cold light to stimulate the macular area, promote cell metabolism and repair, and relieve the symptoms of macular disease; Accelerate tissue regeneration and repair, and improve vision [13,51,52] Xerophthalmia Let the patient be exposed to sunlight, about 20-30 min each time, 1-2 times a day, gradually adapt to; LED light source (830 nm)-LLLT and LED (633 ± 10 nm) are used to directly irradiate the area around the eye to promote the regeneration of corneal nerve and secretion of lacrimal gland, so as to improve the symptoms of dry eye disease; Through infrared stimulation of the eyes and tear glands, increase tear secretion and improve the quality of tear film, thereby relieving dry eye symptoms Improve corneal nerve function: Light can stimulate eye nerve endings, enhance nerve conduction speed, and improve the function of the nervous system, thus relieving dry eye symptoms. Promote tear production: Activates the tear glands and increases tear production, improves tear quality and reduces the risk of eye inflammation and infection [53,54] (Continues)…”
Section: Frequency and Wavelength Principle Applicationmentioning
confidence: 99%